BRAIN DISEASES AMONG MIDDLE-AGED PEOPLE: SYMPTOMS AND TREATMENT APPROACHES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides a comprehensive analysis of common brain diseases among middle-aged individuals, including their main symptoms, diagnosis, and modern treatment methods. Research shows that neurological disorders are most prevalent in the 40-60 age group. This paper includes detailed scientific and practical information on early detection, prevention, and effective treatment approaches for these diseases.